Establishing the CRISPR/Cas13a genome editing system in Nicotiana benthamiana for RNA targeting applications - Robertson, Gaëlle (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.